A Leap over History: Vladimir Jabotinsky's Political Paradigms, 1916–1940. Issue 1 (1st March 2021) - Horowitz, Brian
Abstract: This article argues that Vladimir Jabotinsky envisioned 'leaping over history' to immediately achieve his goal of creating a Jewish majority in Eretz Israel. On several occasions he tried to break with evolutionary time and make events bend to his will. My arguments show him to be a revolutionary political thinker similar to Lenin, Stalin, or Mussolini, rather than a gradualist and parliamentarian. Looking at his career from this angle permits one to create a different timeline that pits Jabotinsky's feverish activity against the slow progress of the Zionist movement.